The Effect of Montessori Method on Students' Vocabulary Achievement A Case Study of SMPS Kartika Kendari - Nilariastuti, Sitti; Nurnia, Nurnia; Suhartini, Lelly (Journal of Teaching English, 2019)
This research aims at investigating the effect of Montessori Method on student’s vocabulary achievement at seventh grade in SMPS Kartika Kendari. The design of the research was quasi-experimental that consists of experimental class and control class. The sample was second semester students class VII.B as experiment class and class VII.C as control class. Both class consisted of 28 students. It was vocabulary test that consisted of 21 numbers of questions and used SPSS 16 to analyze the data. The result shows that there is a significant effect of using Montessori Method on student’s vocabulary achievement. It is proven by descriptive analysis in which student’s mean score of experimental class was 38.20 in pre-test and 76.00 in post-test, meanwhile students’ mean score of control class was 36.20 for pre-test and 68.40 for post-test. Furthermore, The Result of hypothesis testing show that the value of sig (2-tailed) was 0,009 which smaller than 0.05, means that HO is rejected and H1 accepted. Therefore, it can be inferred that there is a significant effect using Montessori Method on student’s vocabulary achievement. Hence, teaching and learning vocabulary through Montessori Method is one of effective ways in improving student’s vocabulary achievement